Biomarkers of oxidative DNA damage repair in urine - Roszkowski, Krzysztof (Contemporary Oncology/Współczesna Onkologia, 2002)
In a normal human cell there is a steady accumulation of DNA lesions with time. Substantial parts of these lesions are due to endogenous factors that damage DNA. It has been shown that free radicals, attack upon DNA generates a whole series of DNA damage, among them modified bases. Hydroxyl radical (·OH) attack on DNA leads to a large number of pyrimidine- and purine-derived base damage. Some of these modified DNA bases have considerable potential to damage the integrity of the genome. It is generally accepted that the products of repair of 8-oxoGua in cellular DNA are excreted into the urine without further metabolism. There is a common belief that the presence of the modified nucleoside (8-oxodGuo) in urine represents the primary repair product of the oxidative DNA damage in vivo, presumably nucleotide excision repair (NER). However, oxidatively damaged DNA bases are mostly repaired by the base excision repair pathway (BER) although the nucleotide excision repair pathway may also play a role in the repair of some oxidised bases in DNA. Therefore, the assays, which are able to determine the level of 8-oxodGuo as well as the amount of 8-oxoGua in urine, may better reflect oxidative damage of cellular DNA. The analysis of 8-oxoGua in urine presents particular difficulties and until recently there has been no reliably assay for its detection. Recently a new technique was developed which allowed for simultaneous determination of 8-oxodGuo and 8-oxoGua in the same urine sample. This method involved a HPLC prepurification followed by gas chromatography with isotope dilution mass spectrometric detection. Since the level of the modified nucleoside/base in urine may be a good indicator of oxidative DNA insult, and as a general index of oxidative stress. This review article presents data, which suggest some relationship between the level of 8-oxoGua and 8-oxodGuo in human urine and: age, note of metabolism, extent of physical exercise, smoking of tobacco, of diet and development of cancer.